1999
DOI: 10.1046/j.1365-2141.1999.01226.x
|View full text |Cite
|
Sign up to set email alerts
|

Transferrin receptor on peripheral blood lymphocytes in iron deficiency anaemia

Abstract: Summary. The effect of iron deficiency anaemia (IDA) on CD71 expression by peripheral blood lymphocytes was studied in 43 children with iron deficiency anaemia. 18 healthy age-matched children were selected as the control group. 11 children with b-thalassaemia trait were also studied. Lymphocytes bearing CD71 were enumerated by flow cytometric analysis of peripheral blood. At diagnosis, CD71 þ peripheral lymphocytes (mean Ϯ SE) was 5·90 Ϯ 0·76% in patients with IDA and 12·60 Ϯ 0·98% in healthy controls (P ¼ 0·… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
(26 reference statements)
0
5
1
Order By: Relevance
“…Although some investigators have not found differences in the activation status of peripheral blood lymphocytes [3,4,5,6,7], our results clearly show that our patients, with transfusion-dependent thalassemia, have increased numbers of activated peripheral blood cells. The majority of our patients have received more than 50 blood units throughout their life, and no correlation was found between the activation status and the number of transfusions.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…Although some investigators have not found differences in the activation status of peripheral blood lymphocytes [3,4,5,6,7], our results clearly show that our patients, with transfusion-dependent thalassemia, have increased numbers of activated peripheral blood cells. The majority of our patients have received more than 50 blood units throughout their life, and no correlation was found between the activation status and the number of transfusions.…”
Section: Discussioncontrasting
confidence: 44%
“…It is known that thalassemia patients suffer from immunomodulation, including alterations in lymphocyte subsets, abnormal levels of cytokines, and the presence of alloantibodies [1,2,3,4,5,6,7]. It has been reported that thalassemia children have decreased levels of natural killer cells and increased activation of the expression of interleukin (IL) 2 receptor (CD25), HLA-DR, and CD45RO on lymphocytes [7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The increased percentage of T lymphocytes expressing the transferrin receptor observed by us contrasts with the marked reduction in the percentage of total lymphocytes expressing CD71 on children with severe anemia [21]. The conflicting results may be explained by the degree of iron deficiency.…”
Section: Discussionmentioning
confidence: 73%
“…Lymphocytes were studied totally and T–B lymphocyte separation was not applied. In a study by Kinik et al. (1999), CD71 expression on peripheral lymphocytes was found to be significantly low in the group with IDA, but the stimulation with PHA had not been applied.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have evaluated the effects of TfR expression in IDA. In two of them, a decrease was detected in TfR expression on peripheral lymphocytes (Aydar, Buyukkececi & Kulali, 1998; Kinik, Tuncer & Altay, 1999). In addition it was also shown that TfR expression increased with 30‐day iron treatment (Kinik et al.…”
Section: Introductionmentioning
confidence: 99%